The Political Map of the World and its Specific Features - Eshmamatovich, Boymatov Bahrom (Universitas Muhammadiyah Sidoarjo, 2022)
The article discusses the world political map and its specific aspects, including quantitative changes in the world political map, qualitative changes, political and geographical changes on the map, evolutionary, revolutionary, military -Political conditional changes are briefly studied.